2018
DOI: 10.1055/a-0608-4635
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Two Training Programs on Transcriptional Levels of Neurotrophins and Glial Cells Population in Hippocampus of Experimental Multiple Sclerosis

Abstract: The aim of the present study was to investigate the effects of high-intensity interval training (HIIT) versus low-intensity continuous training (LICT) on transcriptional levels of neurotrophic factors and oligodendrocyte/microglia cell loss in a cuprizone (CP) induced animal model of demyelination. Male C57BL/6 mice were assigned to six groups: control (C), cuprizone-induced demyelination (CP), interval training (IT), continuous training (CT), IT plus CP (ITCP), and CT plus CP (CTCP). Training programs on the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 78 publications
1
17
0
Order By: Relevance
“…Most studies in nonobese subjects have reported higher BDNF and TrkB expression during low-intensity exercise than high-intensity exercise (Ghodrati-Jaldbakhan et al, 2017;Shih et al, 2013). Some studies have reported that high-intensity interval training is more effective for BDNF expression in the hippocampus than continuous low-intensity exercise (Freitas et al, 2018;Naghibzadeh et al, 2018). However, no studies have been conducted to determine which exercise intensity was most effective in improving BDNF and TrkB expression and cognitive function by performing tests with various exercise intensities with HFDs.…”
Section: Introductionmentioning
confidence: 99%
“…Most studies in nonobese subjects have reported higher BDNF and TrkB expression during low-intensity exercise than high-intensity exercise (Ghodrati-Jaldbakhan et al, 2017;Shih et al, 2013). Some studies have reported that high-intensity interval training is more effective for BDNF expression in the hippocampus than continuous low-intensity exercise (Freitas et al, 2018;Naghibzadeh et al, 2018). However, no studies have been conducted to determine which exercise intensity was most effective in improving BDNF and TrkB expression and cognitive function by performing tests with various exercise intensities with HFDs.…”
Section: Introductionmentioning
confidence: 99%
“…FE has been tested in CPZ model (40, 41). Two treadmill-based protocols, the high-intensity interval training (HIIT) and the low-intensity continuous training (LICT), started 4 weeks before CPZ feeding, reduced motor deficits of CPZ-injured animals and increased the mRNA of neurotrophic factors in the hippocampus.…”
Section: Immune Players In Ms Pathogenesismentioning
confidence: 99%
“…Other studies have investigated the interactions between exercise and oligodendrocyte repopulation in models of MS (Jensen et al, 2018;Kim & Sung, 2017;Naghibzadeh, Ranjbar, Tabandeh, & Habibi, 2018). The first study examined whether exercise improved longterm memory deficits and hippocampal neuroplasticity in EAE mice (Kim & Sung, 2017).…”
Section: Significancementioning
confidence: 99%
“…The second study investigated the effects of prior exerciseeither high-intensity interval training or low-intensity continuous training-on oligodendrocyte loss in young male C57BL/6 mice following cuprizone demyelination (Naghibzadeh et al, 2018). After 4 weeks of forced treadmill exercise, mice were fed 0.2% cuprizone to induce demyelination and then exercised for 5 more weeks before sacrifice.…”
Section: Significancementioning
confidence: 99%
See 1 more Smart Citation